2022
DOI: 10.1093/humrep/deac147
|View full text |Cite
|
Sign up to set email alerts
|

Associations between epigenetic age acceleration and infertility

Abstract: STUDY QUESTION Is the use of ART, a proxy for infertility, associated with epigenetic age acceleration? SUMMARY ANSWER The epigenetic age acceleration measured by Dunedin Pace of Aging methylation (DunedinPoAm) differed significantly between non-ART and ART mothers. WHAT IS KNOWN ALREADY Among mothers who used ART, epigenetic age acceleration may be associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
(98 reference statements)
0
8
1
Order By: Relevance
“…In a group of n = 181 infertile patients aged 37-39 years, we could confirm that women who subsequently conceived and delivered after ART were epigenetically younger than those who did not (respectively: 36.1 ± 4.2 and 37.3 ± 3.3 years, p < 0.04). In contrast with Monseur et al and Lee et al (Monseur et al, 2020;Lee et al, 2022), we verified that adjusting for the variables that differed between the two groups (AFC, FSH, number of oocytes retrieved) the difference remained statistically significant (p = 0.028). Although these findings should be considered with caution for some aspects (restricted patients' age, choice of the epigenetic model), they suggest that the contribution of epigenetic clocks may not be limited to reflect ovarian reserve.…”
Section: Results From Peripheral Leukocytescontrasting
confidence: 71%
See 4 more Smart Citations
“…In a group of n = 181 infertile patients aged 37-39 years, we could confirm that women who subsequently conceived and delivered after ART were epigenetically younger than those who did not (respectively: 36.1 ± 4.2 and 37.3 ± 3.3 years, p < 0.04). In contrast with Monseur et al and Lee et al (Monseur et al, 2020;Lee et al, 2022), we verified that adjusting for the variables that differed between the two groups (AFC, FSH, number of oocytes retrieved) the difference remained statistically significant (p = 0.028). Although these findings should be considered with caution for some aspects (restricted patients' age, choice of the epigenetic model), they suggest that the contribution of epigenetic clocks may not be limited to reflect ovarian reserve.…”
Section: Results From Peripheral Leukocytescontrasting
confidence: 71%
“…Attention should be addressed to the trimester considered. The DNAm GA proposed by Mayne et al was based on I-II trimester healthy pregnancy, that could conceal later adverse events in III trimester (Mayne et al, 2017) while on the opposite way, the clock by Lee et al may encompass Frontiers in Cell and Developmental Biology frontiersin.org some biases due to the training set based on III trimester (Lee et al, 2022). Not at last, as studies in twin pregnancies GA acceleration showed that heritability reached only 57%, environmental factors should be taken into account in the data analysis (Tekola-Ayele et al, 2019).…”
Section: Results From Placentamentioning
confidence: 99%
See 3 more Smart Citations